A Study on Credit Card Holders’ Expectations and Preferences towards Selected Banks in Coimbatore City, Tamil Nadu - Kumaresan, A.; Chitrakala, I.; Gowtham, K. (Indian Journal of Marketing, 2010)
While the movement against the use of plastic is gaining momentum, one industry that is surging ahead is the credit cards industry. Today, the Indian population feels that a wallet without a card is empty. During the last one decade, there has been an exponential growth in the issue of credit cards and their usage.